UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL 50% BIJI PINANG (Areca catechu) DENGAN METODE DPPH (2,2-diphenyl-1-picryhydrazyl) - Humaryanto; Fathnur Sani K; Yuliawati Yuliawati; Ave Olivia Rahman; Muhaimin Muhaimin (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2023)
Areca nut is a plant that contains secondary chemical metabolites of flavonoids, alkaloids, tannins, terpenoids, and steroids. Where content has activity as an antioxidant. The aim of this study were to determine the antioxidant activity of 50% ethanol extract of areca nut against DPPH free redicals based on the IC50 value. Extraction method using 50% ethanol with maceration method. The antioxidant activity test was made with 5 concentration series, namely 10 ppm, 50 ppm, 100 ppm, 150 ppm, and 200 ppm. The extract was tested for free radical scavenging against DPPH (2,2-diphenyl-1-picrylhydrazyl) with a wavelength of 517 nm using a UV-Vis spectrophotometer. The comparator used is Vitamin C. The results showed that the 50% ethanol extract of areca nut has a very strong category of antioxidant activity with an IC50 value of 27,565 ppm, while a positive control of Vitamin C has an IC50 value of 28,546 ppm. The conclusion obtained from the above results is that 50% ethanol extract has very strong antioxidant activity.